FLEXURAL PERFORMANCE AND DESIGN EVALUATION OF REINFORCED CONCRETE BEAMS WITH STEEL REINFORCEMENT AND BASALT FIBER-REINFORCED POLYMER LONGITUDINAL BARS: Flexural Performance of Concrete Beams Reinforced with BFRP and Steel Bars - Hallem, Saif; Khalid, Nibras (Journal of Applied Engineering Science, 2026)
This study experimentally and analytically investigates the flexural behaviour of RC beams reinforced with either conventional steel longitudinal bars or basalt fibre-reinforced polymer (BFRP) longitudinal bars in combination with steel stirrups. Eight simply supported beam specimens were tested under monotonic static loading, comprising two distinct reinforcement systems: steel-reinforced control beams and BFRP-reinforced beams. The experimental program evaluated reinforcement and concrete strains, mid-span deflections, cracking behaviour, ultimate load capacity, and elastic energy storage prior to failure. The results indicate that steel-reinforced beams exhibited ductile flexural failure characterized by steel yielding followed by gradual concrete crushing, enabling controlled crack development and deformation. In contrast, beams reinforced with BFRP longitudinal bars failed in a more brittle manner governed by concrete crushing, reflecting the linear-elastic response of BFRP reinforcement, while exhibiting larger deflections and higher concrete strain levels. Despite these differences in failure mode and ductility, BFRP-reinforced beams achieved comparable or higher ultimate load capacities relative to their steel-reinforced counterparts. Analytical predictions based on ACI 440.2R-08 showed good agreement with experimental results, with conservative underestimations of ultimate capacity (ACI/Exp ratios ranging from 0.93 to 0.97), confirming the reliability of current design provisions. The findings highlight the inherent trade-offs between stiffness, ductility, and load-carrying capacity associated with steel and BFRP reinforcement systems and emphasize the importance of serviceability considerations in BFRP-reinforced RC beam design.
Keywords: RC Beams; Structural Performance; BFRP; Load-Carrying Capacity; Stiffness and Strength; Hybrid Reinforcement